OUTCOME OF DECOMPRESSIVE CRANIECTOMY (DC) FOR SEVERE TRAUMATIC BRAIN INJURY (STBI) IN ADULTS: Decompressive Craniectomy (DC) - Qasmi, Shahzad Ahmed; Ghaffar, Abdul; Hussain, Zahid; Akram, Maqsood (Pakistan Armed Forces Medical Journal, 2015)
Objective: To evaluate the outcomes of decompressive craniectomy (DC) in adults with severe traumatic brain injury (STBI).Study Design: Observational cross-sectional.Place and Duration of Study: Neurosurgical unit CMH Rawalpindi from July, 2011 to June 2014.Material and Methods: Total of 39 patients who underwent DC for STBI were included in the study. Patients of both sexes and of age range 20 – 48 (32.03 ± 8.01) years were included in the study. The DC was performed within 24 and after 24 hours. Parameters recorded were mortality, neurological outcome / complications like brain herniation, wound dehiscence, cerebrospinal fluid (CSF) leak, contusion expansion, sinking flap syndrome, subdural hygromas and hydrocephalus. Data was analyzed by using SPSS version 17 and descriptive statistics, frequency, rate and percentage was computed for presentation of qualitative outcomes.Results: Favourable neurological outcome was seen in 21 patients (53.85%) where as 6 patients (15.38%) had moderate to severe disability and 3 patients (7.69%) were vegetative respectively. Patients operated within 24 hours and with Glasgow coma scale (GCS) range 6-8 had better outcome. . Overall 9 patients (23.08%) did not survive the injury and procedure.Conclusion: As high mortality is associated with STBI, DC is an effective option to lower down the refractory intracranial hypertension with an acceptable surgical outcome.